Exome Sequencing in BRCA1-2 Candidate Familias: The Contribution of Other Cancer Susceptibility Genes - Doddato, Gabriella; Valentino, Floriana; Giliberti, Annarita; Papa, Filomena Tiziana; Tita, Rossella; Bruno, Lucia Pia; Resciniti, Sara; Fallerini, Chiara; Benetti, Elisa; Palmieri, Maria; Mencarelli, Maria Antonietta; Fabbiani, Alessandra; et al. (Frontiers in Oncology, 2021)
Hereditary Breast and Ovarian Cancer (HBOC) syndrome is a condition in which the risk of breast and ovarian cancer is higher than in the general population. The prevalent pathogenesis is attributable to inactivating variants of the BRCA1-2 highly penetrant genes, however, other cancer susceptibility genes may also be involved. By Exome Sequencing (ES) we analyzed a series of 200 individuals selected for genetic testing in BRCA1-2 genes according to the updated National Comprehensive Cancer Network (NCCN) guidelines. Analysis by MLPA was performed to detect large BRCA1-2 deletions/duplications. Focusing on BRCA1-2 genes, data analysis identified 11 cases with pathogenic variants (4 in BRCA1 and 7 in BRCA1-2) and 12 with uncertain variants (7 in BRCA1 and 5 in BRCA2). Only one case was found with a large BRCA1 deletion. Exome analysis allowed to characterize pathogenic variants in 21 additional genes: 10 genes more traditionally associated to breast and ovarian cancer (ATM, BRIP1, CDH1, PALB2, PTEN, RAD51C, and TP53) (5% diagnostic yield) and 11 in candidate cancer susceptibility genes (DPYD, ERBB3, ERCC2, MUTYH, NQO2, NTHL1, PARK2, RAD54L, and RNASEL). In conclusion, this study allowed a personalized risk assessment and clinical surveillance in an increased number of HBOC families and to broaden the spectrum of causative variants also to candidate “non-canonical” genes.